A meta-analysis on associations between vitamin D receptor genetic variants and tuberculosis. (May 2019) - Wang, Yan; Li, Hong-jie
Abstract: Objectives: We aimed to analyze potential associations between vitamin D receptor ( VDR ) genetic variants and tuberculosis (TB) through a meta-analysis. Methods: Systematic literature research of PubMed, Web of Science, Embase and CNKI was performed to identify eligible articles. Statistical analyses were conducted by using Review Manager. Results: Totally 54 studies were enrolled for analyses. Pooled overall analyses suggested that VDR rs1544410 (dominant model: p = 0.02; allele model: p = 0.04), rs2228570 (recessive model: p = 0.01; allele model: p = 0.03) and rs731236 (recessive model: p = 0.02; allele model: p = 0.02) variants were significantly associated with TB. Further subgroup analyses by ethnicity revealed that rs1544410 variant was significantly associated with TB in South Asians (dominant and allele models) and Caucasians (dominant, recessive and allele models), rs2228570 variant was significantly associated with TB in East Asians (recessive model), and rs731236 variant was significantly associated with TB in South Asians (dominant, recessive and allele models). Conclusions: Our meta-analysis suggested that VDR rs1544410, rs2228570 and rs731236 variants might serve as genetic biomarkers of TB in certain populations. Highlights: This is so far the most comprehensive evidence-based meta-analysis on VDR variants and TB. VDR rs1544410, rs2228570 and rs731236 variants were all associated with TB in certain ethnicities. Future investigations need to explore potential roles of other VDR variants in TB.